Effects of the early administration of sivelestat sodium on bronchopulmonary dysplasia in infants: A retrospective cohort study. (December 2017) - Ogawa, Ryo; Mori, Rintaro; Iida, Koichi; Uchida, Yumiko; Oshiro, Makoto; Kageyama, Misao; Kato, Yuichi; Tanaka, Taihei; Nakata, Yusei; Nishimura, Yutaka; Hokuto, Isamu; Bonno, Motoki; et al.
Abstract: Background: Chorioamnionitis, or infiltration of the chorioamnion by neutrophils, is a risk factor associated with the development of bronchopulmonary dysplasia. Increased neutrophil elastase levels are observed in the tracheal aspirates of these patients. Aims: To examine the effects of early administration of the selective neutrophil elastase inhibitor sivelestat, which is used to treat acute lung injury in adults, on bronchopulmonary dysplasia in extremely premature infants. Study design: Retrospective cohort study. Subjects: This study included extremely low-birth-weight infants born at a gestational age < 28 weeks. Patients were divided into groups based on the receipt of sivelestat. Outcome measures: The primary outcome was the rate of bronchopulmonary dysplasia-free survival at a postmenstrual age of 36 weeks, and the secondary outcomes included various clinically significant factors of neonatal mortality and morbidity and adverse events. Results: Of the 1031 included neonates, 124 (12.0%) were treated with sivelestat. Significant differences between the groups were noted for gestational age, delivery method, fetal number, the frequency of chorioamnionitis, immunoglobulin M levels, and WBC counts. No differences were identified concerning the bronchopulmonary dysplasia-free survival rate at a postmenstrual age of 36 weeks (adjusted odds ratio for sivelestat to control, 0.83; 95% confidence interval = 0.53–1.30). Secondary outcomes did not significantly differ between the groups. Conclusions: In extremely premature infants, early sivelestat use was not associated with an improved rate of survival without bronchopulmonary dysplasia at a postmenstrual age of 36 weeks. Highlights: Sivelestat, a selective neutrophil elastase inhibitor, has been proposed for prevention of bronchopulmonary dysplasia. Sivelestat is not associated with neonatal death or any adverse effects. Sivelestat is not associated with an improvement in survival without bronchopulmonary dysplasia.